Strategic inventories under limited commitment. (9th July 2019) - Antoniou, Fabio; Fiocco, Raffaele
Abstract: In a dynamic storable good market where demand changes over time, we investigate the producer's strategic incentives to hold inventories in response to the possibility of buyer stockpiling. The literature on storable goods has demonstrated that buyer stockpiling in anticipation of higher future prices harms the producer's profitability, particularly when the producer cannot commit to future prices. We show that the producer's inventories act as a strategic device to mitigate the loss from the lack of commitment. Our results provide a rationale for the producer's inventory behavior that sheds new light on the well‐documented empirical evidence about inventories.